PPARγ in Bacterial Infections: A Friend or Foe? - Reddy, Aravind T. (PPAR Res, 2016)
Peroxisome proliferator-activated receptor γ (PPARγ) is now recognized as an important modulator of leukocyte inflammatory responses and function. Its immunoregulatory function has been studied in a variety of contexts, including bacterial infections of the lungs and central nervous system, sepsis, and conditions such as chronic granulomatous disease. Although it is generally believed that PPARγ activation is beneficial for the host during bacterial infections via its anti-inflammatory and antibacterial properties, PPARγ agonists have also been shown to dampen the host immune response and in some cases exacerbate infection by promoting leukocyte apoptosis and interfering with leukocyte migration and infiltration. In this review we discuss the role of PPARγ and its activation during bacterial infections, with focus on the potential of PPARγ agonists and perhaps antagonists as novel therapeutic modalities. We conclude that adjustment in the dosage and timing of PPARγ agonist administration, based on the competence of host antimicrobial defenses and the extent of inflammatory response and tissue injury, is critical for achieving the essential balance between pro- and anti-inflammatory effects on the immune system.